“The place is a prison, and you can’t change it”: Rehabilitation, Retraining, and Soldiers’ Re-Establishment at Speedwell Military Hospital, Guelph. 1911-1921 - Durham, Brook (Ontario History)

(untitled) (The Ontario Historical Society, 2017)
Speedwell Military Hospital was a hospital for veterans of the Canadian Expeditionary Force located in the newly-built Ontario Reformatory in Guelph. Speedwell was part of a nation-wide program administered by the Department of Soldiers’ Civil Re-Establishment (DSCR) during the First World War intended to neutralize some of the social dangers associated with demobilization. As the health of individual veterans at Speedwell became closely associated with the nation’s economic strength, the ultimate goal of hospitals like Speedwell was the transformation of sick and wounded veterans into healthy and productive workers. However, as the needs of patients changed after the war, the initial promise of Speedwell as a site of rehabilitative labour made it clearly unsuitable for veterans in need of long-term convalescence care.